Hydrocarbon charge history of deeply buried clastic reservoirs in the Bozi area of the Kuqa Depression, western China: implications for deep and ultra-deep petroleum exploration - Yang, Peng; Song, Yaya; Liu, Keyu; Wang, Shunyu; Wei, Xinzhuo; Liu, Jianliang (Frontiers in Earth Science, 2024)
Significant progress has recently been made in deep and ultra-deep oil and gas exploration globally, demonstrating enormous exploration potential of the deep and ultra-deep strata. However, the accumulation and preservation pattern of deep and ultra-deep oil and gas remains poorly understood, greatly impeding further petroleum exploration and development in the deep and ultra-deep strata. By taking the Bozi deep and ultra-deep condensate gas reservoirs in the Kuqa Depression, western China as an example, we attempt to reconstruct the hydrocarbon charge history in such deep reservoirs via an integrated investigation involving quantitative grain fluorescence, fluid inclusion petrography and microthermometry, micro-fluorescence spectroscopy, laser Raman spectroscopy, PVTx modelling, and basin modelling. The results show that: (1) The Bozi deep and ultra-deep reservoirs contain one group of gas inclusion assemblage, and two groups of oil inclusion assemblages, with one being characterized by near yellowish-whitish and blue-whitish diphasic or triphasic oil inclusions, and the other being featured by bright blue diphasic oil inclusions; (2) The first oil charge occurred during the Early Neogene (6.5–5.5 Ma), and the second oil charge occurred during the Late Neogene (4.4–3.5 Ma), under normal hydrostatic pressure or slightly weak overpressure; and (3) The gas charge occurred during the Pleistocene (∼1.6 Ma), with a corresponding reservoir pressure coefficient of approximately 1.7, transforming the reservoir fluid phase state from black oil or volatile oil to condensate gas. Our findings highlight that aside from the present burial depth, a favorable burial history model is crucial for the preservation of liquid hydrocarbons in deep and ultra-deep reservoirs. The occurrence of liquid hydrocarbons in the Bozi deep and ultra-deep condensate gas reservoirs with depths over 7,000 m is benefited from a prolonged period (>100 Ma) of shallow burial and a late-stage (since 10 Ma) rapid subsidence.